ANALYSIS OF RICE CROP PRODUCTION CHANGES DUE TO LAND USE CHANGES IN BAGIK POLAK VILLAGE, LABUAPI SUBDISTRICT WEST LOMBOK REGENCY - Siddiqirly, Muhammad; Ningsi, Maulina; Mukmina, Mukmina; Putri, Mega Utami Regina; Selvia, Siska Ita (Fakultas Pertanian Universitas Mataram, 2023)
Bagik Polak Village is located in Labuapi District, West Lombok Regency. Its area is 2.50 km2 with 7 sub-villages and a population of 4,232 people and a population density of 1,693 people/km2. Geographically, Bagik Polak is located at coordinates 8037'39